Recommended best management practices for Arkansas Canyon stickleaf (Nuttallia densa): practices developed to reduce the impacts of road maintenance activities to plants of concern - Smith, Gabrielle, author; Panjabi, Susan Spackman, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
Arkansas Canyon stickleaf (Nuttallia densa) is a small, yellow-flowered, subshrub in the Loasaceae (Blazingstar Family) that is known only from the Upper Arkansas River Basin in Fremont and Chaffee counties, Colorado, and is considered to be imperiled at a global and state level (G2/S2; Colorado Natural Heritage Program 2014). One of the biggest conservation issues for this imperiled plant species is the lack of awareness of its existence and status. Avoiding or minimizing impacts to this species during road maintenance activities will effectively help to conserve its habitat and is unlikely to confer substantial impacts on road maintenance goals and projects. The Best Management Practices (BMPs) included in this document are intended to help increase the awareness of this species for anyone involved in road maintenance activities. The desired outcome of these recommended BMPs is to reduce significantly the impacts of road maintenance activities to the Arkansas Canyon stickleaf on federal, state, and/or private land. The BMPs listed here are intended to be iterative, and to evolve over time as additional information about the Arkansas Canyon stickleaf becomes available, or as road maintenance technologies develop. The intent of these BMPs is to inform people working along roadside areas regarding the importance of Arkansas Canyon stickleaf, one of Colorado's botanical treasures, and to outline some of the ways in which this species can coexist with road maintenance activities. The implementation of these recommendations will help to assure that maintenance activities proceed without unintended harm to the Arkansas Canyon stickleaf.
Prepared for: Colorado Department of Transportation and the Colorado Natural Areas Program.
May 2014.
Keywords: plant habitat; noxious weed management; Arkansas Canyon stickleaf; species profile